Evolution of madness - Johnson, Michael, 1953-; Gary Whiteaker Corporation (Cahokia, IL : GWC, 1999)
In this eye-opening video for the therapeutic staff, Michael Johnson emphasizes how the dynamics surrounding today's addict are different from the addict of twenty years ago. He takes the viewer through the evolution of addiction, with emphasis on the character, thought processes, value system and objectives of today's addict
Michael Johnson
Keywords: Substance-Related Disorders -- psychology; Substance-Related Disorders -- etiology; Behavior, Addictive -- psychology; Behavior, Addictive -- etiology